Absorption Proprieties of Rhodamine 6G (Rh-6G) Laser Dye doped in SolGel glass - Laxman V. Jathar , Pravin Pawar , Milind J. Kulkarni (Cuestiones de Fisioterapia, 2024)
Nanoporous glass samples are prepared by using sol-gel technology mainly which consisthydrolysis and poly condensation of tetraethyl orthosilicate (TEOS) using HCl as catalystat low/room temperature. The prepared glass samples are highly nano porous, opticallypurely transparent, mechanically and thermally stable and therefore organic dye moleculesor any other biological materials can be incorporated in this gel network, with no risk ofthermal degradation, whereas conventional glass production requiring high temperaturewhich organic molecules cannot withstand.